The impact of electronic word-of-mouth and perceived value on Iphone users' repurchase intention: The mediating role of brand trust - Raka, Anyelir; Abror, Abror (Universitas Negeri Padang, 2025)
This study examines the factors that influence repurchase intention on iPhone users in Padang, focusing on the role of Electronic Word of Mouth (eWOM), perceived value, and brand trust. This study aims to determine the impact of eWOM on brand trust and repurchase intention, examine the influence of perceived value on brand trust and repurchase intention, and examine the mediating role of brand trust in the relationship. The sample used was 186 respondents. Data were processed using SmartPLS and collected through an online questionnaire. The results of the study indicate that (1) eWOM has a positive and significant effect on brand trust. (2) eWOM has a positive and significant effect on repurchase intention. (3) Perceived value has a positive and significant effect on brand trust. (4) Perceived value has a positive and significant effect on repurchase intention. (5) Brand trust has a positive and significant effect on repurchase intention. (6) eWOM has a positive and insignificant effect on Repurchase Intention mediated by Brand Trust. (7) Perceived value has a positive and significant effect on Repurchase Intention mediated by Brand Trust.